Perancangan Prototype Mesin Pengayak Pasir Semi Otomatis Menggunakan Photovoltaic - Dionisia Rue; Irrine Budi Sulistiawati; Ni Putu Agustini (Universitas Darul Ulum, 2021)
The sand sieving system is generally still done manually which requires full human power for the sieving process. This is quite time consuming and the resulting fine sand mass is far from what is required for a construction project. Therefore the author made the idea of ​​​​designing a sand sieving machine that can be applied anywhere. This machine uses a driving system of a Brushless Direct Current electric motor with a capacity of 350W as the driving motor. Brushless Direct Current Motor is used because it has the advantage of a large starting torque, higher speed because it does not use a brush. As a source of electricity, new renewable energy solar panels with a capacity of 400Wp are used which are more environmentally friendly and efficient. This machine works when the solar panels supply a power source to the driving motor and then transmitted by the chain and gear to the sieve tube for the sieving process. This machine has a faster sand sieving process than manual sieving and the type of motor used is more efficient.